An Overview of Public Sector Budget Monitoring & Evaluation Systems for Gender Equality: Lessons from Uganda and Rwanda - Sikhosana, Nqobile; Nzewi, Ogochukwu (Journal of Reviews on Global Economics, 2019)
Citizen expectations regarding government accountability and transparency are rising around the globe and this has given politicians and public administrators an obligation to account for their actions more regularly than in the past. Although a number of African countries have made notable strides in public expenditure management, citizens` level of trust in government is eroding owing to administrative challenges such as corruption, embezzlement of public funds and ineffective delivery of public services. Against this backdrop, public sector budget monitoring and evaluation has emerged to spur efficiency, effectiveness and transparency within organisations and institutions in relation to meeting developmental goals and outcomes. One of the socio-economic ills prevalent in Africa is the failure to channel resources towards the achievement of gender outcomes as shown by existing gender disparities. Using desktop research, this article responds to this ultimate concern by examining the extent to which Uganda and Rwanda have played a leading role in the implementation of budget M&E to achieve specific gender outcomes. Results show that although a number of countries have transformed their budget monitoring and evaluation mechanisms, only a few have managed to align these systems to gender equality goals.